Nurse attitudes in relation to health care ethics and legal regulations for nursing - Losa Iglesias, Marta Elena; Becerro de Bengoa Vallejo, Ricardo (Acta Bioethica, 2014)
The nursing environment is full of situations under ethical and legal constraints. Therefore this study focused on the knowledge, position and attitudes of nurses in relation to healthcare ethics and nursing legal regulations. We conducted a pretest and posttest study using a specific questionnaire administered to a convenience sample of nurses who worked in a healthcare system in Principado de Asturias, a northern state of Spain and were enrolled in a continuing nursing education program about ethical and legal aspects in the nursing profession. The main findings suggest that nurses are very concerned about situations that create ethical and legal conflicts but do not feel sufficiently trained. In general, they demonstrated sufficient knowledge to address the most frequent ethical and moral situations of nursing work, and the training received during a postgraduate course in ethics and legislation provided them with greater knowledge and tools to solve the dilemmas. In conclusion, although the nurses have university-level education about professional deontology, bioethics and nursing legislation, they require periodic continuing education.